Inhibitory effect of a new orally active cedrol-loaded nanostructured lipid carrier on compound 48/80-induced mast cell degranulation and anaphylactic shock in mice - Chakraborty S (Dove Medical Press, 2017)
Shreyasi Chakraborty, Nabanita Kar, Leena Kumari, Asit De, Tanmoy Bera Laboratory of Nanomedicine, Department of Pharmaceutical Technology, Jadavpur University, Kolkata, West Bengal, India Background: Type I hypersensitivity is an allergic reaction characterized by the overactivity of the immune system provoked by normally harmless substances. Glucocorticoids, anti-histamines, or mast cell stabilizers are the choices of treatment for type I hypersensitivity. Even though these drugs have the anti-allergic effect, they can have several side effects in prolong use. Cedrol is the main bioactive compound of Cedrus atlantica with anti-tumor, anti-oxidative, and platelet-activating factor inhibiting properties.Methods: In this study, the preparation and anti-anaphylactic effect of cedrol-loaded nanostructured lipid carriers (NLCs) were evaluated. NLCs were prepared using Compritol® 888 ATO and triolein as lipid phase and vitamin E D-α-tocopherylpolyethyleneglycol 1000 succinate, soya lecithin, and sodium deoxycholate as nanoparticle stabilizers.Results: The average diameter of cedrol-NLCs (CR-NLCs) was 71.2 nm (NLC-C1) and 91.93 nm (NLC-C2). The particle had negative zeta potential values of –31.9 mV (NLC-C1) and –44.5 mV (NLC-C2). Type I anaphylactoid reaction in the animal model is significantly reduced by cedrol and cedrol-NLC. This in vivo activity of cedrol resulted that cedrol suppressed compound 48/80-induced peritoneal mast cell degranulation and histamine release from mast cells. Furthermore, compound 48/80-evoked Ca2+ uptake into mast cells was reduced in a dose-dependent manner by cedrol and cedrol-NLC. Studies confirmed that the inhibition of type I anaphylactoid response in vivo in mice and compound 48/80-induced mast cell activation in vitro are greatly enhanced by the loading of cedrol into the NLCs. The safety of cedrol and CR-NLC was evaluated as selectivity index (SI) with prednisolone and cromolyn sodium as positive control. SI of CR-NLC-C2 was found to be 11.5-fold greater than both prednisolone and cromolyn sodium.Conclusion: Administration of CR-NLC 24 hours before the onset of anaphylaxis can prevent an anaphylactoid reaction. NLCs could be a promising vehicle for the oral delivery of cedrol to protect anaphylactic reactions. Keywords: mast cell, degranulation, allergy, NLC, cedrol, anaphylaxis